Study on corneal morphology and correlation between corneal thickness and serum uric acid levels in gout - Rishi Sharma; Jaya Kaushik; Ankita Singh; Aatish Saraswat; Sumit Goyal (The Pan-American Journal of Ophthalmology)
Background: Gout is an inflammatory metabolic disorder characterized by the accumulation of monosodium urate in extracellular spaces, especially joints. Its clinical characteristics include arthritis, nephrolithiasis, nephropathy, and tophi. Ocular tophi have been observed in the lateral canthus, upper eyelid, orbit, iris, anterior chamber, subconjunctival space, and cornea. Good visual acuity requires a transparent cornea with healthy endothelial function and stromal layer organization. Reduced corneal transparency in gout patients may be a result of uric acid accumulation in the stroma or endothelial dysfunction. Aims and Objectives: This study aimed to investigate corneal endothelial cell density (ECD), morphology, and central corneal thickness (CCT) in gout patients compared to healthy individuals. Materials and Methods: A retrospective comparative study was conducted on 70 eyes of 35 gout patients and 70 eyes of 35 healthy subjects without gout or any other systemic disease. Detailed ophthalmologic examination was followed by specular microscopy where ECD, average cell area (ACA), coefficient of variation (CV), hexagonality ratio (HEX), and CCT values were recorded and analyzed in gout patients and healthy subjects. Results and Analysis: Mean ECD and HEX values were lower in the gout group than in the control group (P = 0.004 and P = 0.002). CV, standard deviation, ACA, maximum cell area, and CCT values were significantly higher in the gout group than in the control group (P = 0.001, P < 0.001, P = 0.007, P = 0.002, and P = 0.001). A significant positive correlation was found between uric acid levels and CCT (r = 0.355, P = 0.003). Conclusions: The study and monitoring of corneal morphology in gout patients and the correlation between corneal thickness and serum uric acid levels over time may provide insights into disease progression and modifications in drug therapy. Hence, ophthalmic evaluation should be incorporated in the comprehensive management of gout, especially in patients with unexplained ocular symptoms.